Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Let’s say son’s age = S
Dad’s age = D
4 years ago, the son was (S-4) and dad now is three times that so D=3(S-4)
Expand that to get D=3S-12
In 12 years, the son will be (S + 12)
Dad will also be (D + 12) and he will be two times the sons age at that point so:
D + 12 = 2(S + 12)
Expand the right side:
D +12 = 2S + 24
Subtract 12 from both sides:
D = 2S + 12
So now D = 2S + 12 AND
D = 3S - 12
Since both equations equal “D”, they must then equal each other:
2S + 12 = 3S - 12
Do some algebra and you get S = 24
Plug this back into EITHER “D=“ equations to find D
D=2(24) +12
D=60
Dad’s age = D
4 years ago, the son was (S-4) and dad now is three times that so D=3(S-4)
Expand that to get D=3S-12
In 12 years, the son will be (S + 12)
Dad will also be (D + 12) and he will be two times the sons age at that point so:
D + 12 = 2(S + 12)
Expand the right side:
D +12 = 2S + 24
Subtract 12 from both sides:
D = 2S + 12
So now D = 2S + 12 AND
D = 3S - 12
Since both equations equal “D”, they must then equal each other:
2S + 12 = 3S - 12
Do some algebra and you get S = 24
Plug this back into EITHER “D=“ equations to find D
D=2(24) +12
D=60
Answer:
the dad is 60 im not sure about the son
Step-by-step explanation:
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.